ANALYTICAL STUDY OF HINGUL SHODHAN W.S.R. TO BHAVNA OF AADRAK SWARAS - Bamane, *Amol E.; D.Bhadlikar, Devyani (International Journal of Ayurveda and Pharma Research, 2016)
Rasaacharya were well known about the toxic effect produce due to use of mineral in their impure form. For removing this toxic effect they mentioned various Shodhan (purification) processes in their books. Shodhan process plays a very significant role in purification of Rasa dravya like Hingul for internal administration. In this study Shodhan of Hingul by Kshalan process is performed which is mentioned in book of Rasatarangini. Because of the need of purification & standardization in Ayurveda we do ICP-AES for Elemental qualitative analysis Hingul is one of the toxic mineral which is used therapeutically in practice of Ayurveda after proper treatment called as Shodhan. To evaluate the effect of Shodhan of Hingul was asses by the help of ICP-AES test. Sample of raw Hingul, sample of seven times triturated Hingul, sample of Kshalan water after seven time triturated Hingul and sample of after Kshalan of Hingul was given for the qualitative elemental analysis in the ICP-AES test. In this study we want to see the changes after the Shodhan process. And want to see why our text says use of Aadrak swaras for Shodhan of Hingul. After doing the ICP-AES test of a given sample we found elements like Nikel (NI) and Phosporus (P) in the sample Kshalan water. Hence we conclude that some changes happened during the Shodhan process.